Smart Fibres, Fabrics and Clothing - Tao, Xiaoming (Woodhead Publishing, 2011)
This book is intended to provide an overview and review of the fundamentals and latest developments in smart technology for textiles and clothing. It will be essential reading for academics in textile and materials science departments, researchers, designers and engineers in the textiles and clothing product design field.